Alcohol Stimulates Activation of Snail, Epidermal Growth Factor Receptor Signaling, and Biomarkers of Epithelial-Mesenchymal Transition in Colon and Breast Cancer Cells - Forsyth, Christopher B.; Tang, Yueming; Shaikh, Maliha; Zhang, Lijuan; Keshavarzian, Ali (Alcoholism, clinical and experimental research, 2010)
Background:  Alcohol consumption is associated with the risk of progressive cancers including colon and breast cancer. The mechanisms for the alcohol‐induced aggressive behavior of these epithelial cancer cells have not been fully identified. Epithelial–mesenchymal transition (EMT) is a developmental program recently shown to play a role in cancer progression and metastases. We hypothesized that alcohol might promote cancer progression by inducing EMT in cancer cells and tested this hypothesis by assessing alcohol‐stimulated changes in phenotypic markers of EMT as well as the EMT transcription factor Snail and its related cell signaling. Methods:  Colon and breast cancer cell lines and a normal intestinal epithelial cell line were tested as well as colonic mucosal biopsy samples from alcoholic subjects. Cells were treated with alcohol and assessed for EMT‐related changes using immunofluorescent microscopy, western blotting, reporter assays, RT‐PCR, and knockdown of Snail with siRNA. Results:  We show alcohol upregulated the signature EMT phenotypic marker vimentin as well as matrix metalloprotease (MMP)‐2, MMP‐7, and MMP‐9 and cell migration in colon and breast cancer cells—all characteristics of EMT. Alcohol also stimulated nuclear localization of Snail phosphorylated at Ser246, transcription from a Snail reporter plasmid, and Snail mRNA expression by RT‐PCR. Snail siRNA knockdown prevented alcohol‐stimulated vimentin expression. In vivo, Snail expression was significantly elevated in colonic mucosal biopsies from alcoholics. Also, we found alcohol stimulated activation of epidermal growth factor receptor (EGFR) signaling and an EGFR inhibitor blocked alcohol‐induced cell migration and Snail mRNA expression. Conclusions:  Collectively, our data support a novel mechanism for alcohol promoting cancer progression through stimulating the EMT program in cancer cells via an EGFR‐Snail mediated pathway. This study reveals new pathways for alcohol‐mediated promotion of cancer that could be targeted for therapy or prevention of alcohol‐related cancers.